Using the concept of x-intercept, it is found that the correct statement is:
- The x-intercept of the function f is greater than the x-intercept of function g.
What is the x-intercept of a function?
- The x-intercept of a function is the value of x when y = 0.
In this problem, in function f(x), when f(x) = 0, x = 3, hence the x-intercept is x = 3.
Function g(x) is defined by:
[tex]g(x) = 2 + \sqrt[3]{3x + 1}[/tex]
Hence, the x-intercept of g(x) is found as follows:
[tex]g(x) = 0[/tex]
[tex]2 + \sqrt[3]{3x + 1} = 0[/tex]
[tex]\sqrt[3]{3x + 1} = -2[/tex]
[tex](\sqrt[3]{3x + 1})^3 = (-2)^3[/tex]
[tex]3x + 1 = -8[/tex]
[tex]3x = -9[/tex]
[tex]x = -\frac{9}{3}[/tex]
[tex]x = -3[/tex]
The x-intercept of g(x) is -3, which is less than the x-intercept of function f(x), hence, the correct statement is:
- The x-intercept of the function f is greater than the x-intercept of function g.
To learn more about the concept of x-intercept, you can take a look at https://brainly.com/question/24737967